Incorporating Intimacy: The Evocative Story of Francis J. Grimké - Nickel, Mary (Journal of black religious thought, 2022)
This essay tells the story of Francis J. Grimké. It incorporates several crucial strands in American history: chattel slavery, racialized sexual exploitation, early historically black colleges, Jim Crow violence, early organizing against racism, and the Harlem Renaissance. It draws together diverse notables with whom Francis had sustained personal contact: the Grimké sisters, Frederick Douglass, Charles Hodge, W.E.B. DuBois, Ida B. Wells, and Anna Julia Cooper. Grimké’s story certainly deserves telling. But, as I argue in the second part of the essay, his story also offers new insight into the role intimacy can play in the hard work of social criticism.